Immersion in a relaxing virtual reality environment is associated with similar effects on stress and anxiety as heart rate variability biofeedback - Pratviel, Yvan; Bouny, Pierre; Deschodt-Arsac, Véronique (Frontiers in Virtual Reality, 2024)
Practicing guided breathing at 0.1 Hz in virtual reality yields psychological and physiological benefits. Nonetheless, it remains uncertain whether these effects surpass those induced in a realworld setting. Indeed, the potential influence of the virtual environment on perceived stress and anxiety is not yet fully understood. In this experiment, we aimed to compare the effects of heart rate variability biofeedback combining both haptic and visual cues in real and virtual reality settings among the same group of participants. Additionally, to discern whether the psychological benefits arise from viewing an environment in virtual reality or from the act of performing guided breathing in this specific setting, a "control" immersion condition was introduced. 36 healthy sport students (9 females) participated in this study, performing both the real and virtual reality protocols in a randomized order. Anxiety and stress levels were assessed using the STAI-Y questionnaire and a visual analog scale, respectively. Physiological effects were assessed through measures of heart rate variability, and the performance of cardiac coherence was compared between the real and virtual implementations of guided breathing.As expected, both real and virtual reality heart rate variability biofeedback led to similar physiological modulations and cardiac coherence performances. A decrease in stress and anxiety was observed in both protocols, particularly among participants who initially reported higher stress or anxiety levels. However, no additional changes in psychological states were observed when performing guided breathing while immersed in the virtual environment.